Analysis of Self-Directed Learning of Grade X Students of SMA Negeri 15 Surabaya as a Basis for Recommendations for Guidance and Counseling Services - Hilda Hidayatun Nafi'ah; Ayong Lianawati; Alifia Fitri Kurniawati; Andi Wibowo; Dwi Wulansari (Indonesian Journal of Educational Counseling, 2026)
This study aimed to describe the level of Self-Directed Learning (SDL) among tenth-grade students at SMA Negeri 15 Surabaya as a basis for developing guidance and counseling service recommendations. The research employed a quantitative descriptive survey involving 267 students selected through a saturated sampling technique. Data were collected using a 30-item SDL scale covering five indicators: awareness, learning strategies, learning activities, evaluation, and interpersonal skills. The instrument was found to be valid and highly reliable (Cronbach’s Alpha = 0.92). Data were analyzed using descriptive statistics and categorized into high, medium, and low levels. The results showed that 77% of students were in the high SDL category, while 23% were in the medium category, and no students were classified in the low category. Although students generally demonstrated good learning independence, several aspects still require improvement, particularly self-awareness in selecting learning strategies, consistency in learning habits, information processing, self-evaluation, and interpersonal skills. Initial observations also indicated that some students tended to procrastinate, rely heavily on teachers, and show low learning initiative. Therefore, strengthening SDL through guidance and counseling services and active learning strategies is needed to support more balanced and sustainable development of students’ learning independence